2018
DOI: 10.1111/sed.12539
|View full text |Cite
|
Sign up to set email alerts
|

Origins and genesis of loess deposits in central Spain, as indicated by heavy mineral compositions and grain‐size variability

Abstract: The formation of loess deposits strongly depends on the availability of deflatable dust-sized material. Identification of source areas and mechanisms of dust production is essential for an appropriate characterization of related palaeoenvironmental conditions. So far, little research has been done on loess deposits in the Mediterranean region and information about mechanisms of dust production is very rare. In this context, it is not clear from where the loess deposits from the upper Tagus Basin in central Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 70 publications
(112 reference statements)
1
27
0
Order By: Relevance
“…In fact, grains >50 μm could be suspended only if the wind is so strong that a dust storm occurs (Qiang, Chen, Zhang, et al, ). Thus, the changes in the sand fraction in NLK are suitable for evaluating the history of sand dust storm activity and the wind regimes, as the case of loess deposits in the Tagus River Valley, central Spain (Wolf et al, ). The higher percentages of sand fractions in the NLK loess are derived from more frequent stronger winds.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, grains >50 μm could be suspended only if the wind is so strong that a dust storm occurs (Qiang, Chen, Zhang, et al, ). Thus, the changes in the sand fraction in NLK are suitable for evaluating the history of sand dust storm activity and the wind regimes, as the case of loess deposits in the Tagus River Valley, central Spain (Wolf et al, ). The higher percentages of sand fractions in the NLK loess are derived from more frequent stronger winds.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy mineral assemblage data can be used to fingerprint loess deposits and compare them to potential source sediments. However, using heavy mineral distribution assemblages as a provenance proxy may bear the drawback of mixing multiple distinct sources (Mikulčić Pavlaković et al, 2011;Römer et al, 2016;Meng et al, 2019;Wolf et al, 2019). Recently, the advent of single-grain provenance techniques such as detrital zircon U-Pb dating allowed disentangling multiple dust sources and potentially sign specific proto-source terranes (Stevens et al, 2010;Újvári et al, 2012;Fenn et al, 2018;Pańczyk et al, 2020).…”
Section: Sampling and Laboratory Analyses Methodological Background Omentioning
confidence: 99%
“…Because of their sparser accumulation in the landscape, perimediterranean loess remain poorly documented except for some exceptions (Calvo et al, 2016;Profe et al, 2018). Recent studies in the Po plain (Wacha et al, 2018) the Ebro (Boixadera et al, 2015) and Tagus basins (Wolf et al, 2019) in Spain suggested, however, that Pleistocene loess covered vast parts of perimediterranean areas. The Rhône Valley (SE France) also recorded significant loess deposition during the Last Glacial (Bosq et al, 2018).…”
Section: Introductionmentioning
confidence: 99%